2009
DOI: 10.1152/jn.00557.2009
|View full text |Cite
|
Sign up to set email alerts
|

Balance of Inhibitory and Excitatory Synaptic Activity Is Altered in Fast-Spiking Interneurons in Experimental Cortical Dysplasia

Abstract: Cortical dysplasia (CD) is a common cause of intractable epilepsy in children and adults. We have studied rats irradiated in utero as a model of CD to better understand mechanisms that underlie dysplasia-associated epilepsy. Prior studies have shown a reduction in the number of cortical interneurons and in the frequency of inhibitory postsynaptic currents (IPSCs) in pyramidal cells in this model. They have also shown a reduced frequency of spontaneous and miniature excitatory postsynaptic currents (EPSCs) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 54 publications
6
46
0
Order By: Relevance
“…Significant changes in presynaptic function have been reported in models of temporal lobe epilepsy, including a shift from PPD to PPF for inhibitory postsynaptic potentials (IPSPs) in dentate gyrus granule cells of rats with pilocarpine-induced temporal lobe epilepsy (Kobayashi and Buckmaster 2003), and decreased quantal release of GABA, associated with reduced synaptic vesicle density in both pilocarpine and kainate models of temporal lobe epilepsy (Hirsch et al 1999). A similar shift from PPD to facilitation was reported in IPSCs evoked in layer IV FS cells in the irradiated model of cortical dysplasia (Zhou et al 2009). …”
Section: Ppr For Monosynaptic Ipscs Is Increased In Layer V Pyramidalmentioning
confidence: 55%
“…Significant changes in presynaptic function have been reported in models of temporal lobe epilepsy, including a shift from PPD to PPF for inhibitory postsynaptic potentials (IPSPs) in dentate gyrus granule cells of rats with pilocarpine-induced temporal lobe epilepsy (Kobayashi and Buckmaster 2003), and decreased quantal release of GABA, associated with reduced synaptic vesicle density in both pilocarpine and kainate models of temporal lobe epilepsy (Hirsch et al 1999). A similar shift from PPD to facilitation was reported in IPSCs evoked in layer IV FS cells in the irradiated model of cortical dysplasia (Zhou et al 2009). …”
Section: Ppr For Monosynaptic Ipscs Is Increased In Layer V Pyramidalmentioning
confidence: 55%
“…Furthermore, in other sensory systems, the response of morphologically defined neuron subsets to deafferentation depends on their role in the network (e.g., Francis and Manis 2000;Li et al 2009;Zhou et al 2009). Accordingly, here we propose that the vestibular nuclei neuron subsets selected for study should be distinguished by key morphological features, including axonal output, neurotransmitter phenotype, and/or neuron morphology and that these subsets should be analyzed as separate independent groups after peripheral vestibular lesions.…”
mentioning
confidence: 99%
“…Our previous histological studies have demonstrated the loss of both interneurons (Deukmedjian et al 2004;Roper et al 1999;Zhou andRoper 2010, 2011) and GABAergic presynaptic terminals (Zhou and Roper 2010) and an increase of the density of glutamatergic terminals in dysplastic cortex (Zhou and Roper 2010). Electrophysiological studies have further confirmed an imbalance between excitatory and inhibitory synaptic inputs to pyramidal neurons (Chen and Roper 2003;Zhu and Roper 2000) and to GABAergic interneurons in irradiated rats with CD (Xiang et al 2006;Zhou et al 2009a;. The imbalance favors inhibition to result in a decreased excitability in interneurons ; in contrast, it favors excitation to result in an increased excitability in pyramidal neurons (Zhu and Roper 2000).…”
Section: Dysplastic and Immature Cortex Are More Hyperexcitable And Mmentioning
confidence: 87%
“…Immunofluorescence staining was performed as previously described (Zhou et al 2009a(Zhou et al , 2009b. Coronal cortical sections (45 m) were incubated with rabbit anti-TRPC3 polyclonal antibody (2 g/ml; Alomone Labs, Jerusalem, Israel) at 4°C for 72 h and with Alexa Fluor 488 goat anti-rabbit IgG (1:500; Molecular Probes, Invitrogen) for 2.5 h at ϳ23°C.…”
Section: Immunohistochemistrymentioning
confidence: 99%